PEMANFAATAN LIMBAH SERBUK GERGAJI KAYU SEBAGAI SUBTITUSI CAMPURAN BATA RINGAN KEDAP SUARA - Nurmaidah Nurmaidah; R. Exaudi Simon Purba (Portal: Jurnal Teknik Sipil, 2017)
The increasing demand for housing nowadays causes the need for more building materials. It can provide an alternative to exploit industrial waste that is left alone. Wood powder is a waste obtained from sawmills using both machinery and manuals. Sawdust can also be used as a silencer. In this study, wood waste is used for partial substitution of fine aggregate used in light brick making mix. In this study discusses the characteristics of soundproofing with the utilization of wood sawdust waste, PC cement, and sand as its forming material. In this study, wood sawdust used is from North Sumatra with variation of 0%, 20%, and 30% (mass) compositions, while other material compositions are made constant. With a wooden powder size of 0.25 mm - 2.0 mm. For testing of silencer will be made of cylindrical test object with diameter 11 cm and thickness 6 cm as much as 6 specimen. The results of this study indicate that the 30% sawdust mixture in the third variation shows the highest absorption coefficient value of 0.6832 with the frequency of 1000 Hz with absorption coefficient 0.50% and with the velocity of the sound wave indicates 683.2 m / s . From this research, it can be concluded that the greater the percentage of sawdust mixture, the greater the ability to muffle the noise.Keywords: Lightweight soundproof brick, acoustic, absorption, sawdust